PRODUKSI MEDIA TANAM ORGANIK DAN BRIKET ARANG TERBARUKAN SEBAGAI HASIL KONVERSI LIMBAH BAGLOG JAMUR TIRAM - Dewi, Mustika; Kandar, Mamat; Rahmawati, Noor (Abdi Panca Marga, 2024)
ABSTRACT Much baglog waste is produced as a by-product of oyster mushroom cultivation activities carried out by some farmers in Cinanggung village which has not been processed and utilized optimally, thus having a negative impact on the environment. The community service team from the Microbial Biotechnology scientific group, School of Biological Sciences and Technology (KK BM, SITH) Bandung Institute of Technology (ITB) held a community service program in the form of training for the people of Cinanggung Village, Tanjungsari sub-district, Sumedang district, on how to process baglog waste into planting media. organic and renewable charcoal briquettes, and using them as a medium for growing vegetables in the home garden as an effort to increase food security in household capacity. There were 24 participants in this training, involving members of oyster mushroom farming groups and housewives. The training program is preceded by an understanding of the management of cultivated waste, followed by processing the waste into useful products. This training is a manifestation of the concern of SITH ITB lecturers for the residents of the villages around Mount Geulis. The processing of mushroom baglog waste into a plant growing medium and renewable energy in the form of charcoal briquettes is expected to improve the lives of the people of Cinanggung village through the use of plant growing media to support vegetable growing activities in polybags for the yard, at least to be used for family needs to support family food security. It is hoped that this program will make farmers more prosperous and make government programs related to community food security a success, starting from family food security. Keywords: Waste, baglog, oyster mushrooms, fertilizer, briquettes